High-Throughput Sequencing and the Viromic Study of Grapevine Leaves: From the Detection of Grapevine-Infecting Viruses to the Description of a New Environmental Tymovirales Member - Hily, Jean-Michel; Candresse, Thierry; Garcia, Shahinez; Vigne, Emmanuelle; Tannière, Mélanie; Komar, Véronique; Barnabé, Guillaume; Alliaume, Antoine; Gilg, Sophie; Hommay, Gérard; Beuve, Monique; Marais, Armelle; et al. (Frontiers in Microbiology, 2018)
In the past decade, high-throughput sequencing (HTS) has had a major impact on virus diversity studies as well as on diagnosis, providing an unbiased and more comprehensive view of the virome of a wide range of organisms. Rather than the serological and molecular-based methods, with their more ‘reductionist’ view focusing on one or a few known agents, HTS-based approaches are able to give a ‘holistic snapshot’ of the complex phytobiome of a sample of interest. In grapevine for example, HTS is powerful enough to allow for the assembly of complete genomes of the various viral species or variants infecting a sample of known or novel virus species. In the present study, a total RNAseq-based approach was used to determine the full genome sequences of various grapevine fanleaf virus (GFLV) isolates and to analyze the eventual presence of other viral agents. From four RNAseq datasets, a few complete grapevine-infecting virus and viroid genomes were de-novo assembled: (a) three GFLV genomes, 11 grapevine rupestris stem-pitting associated virus (GRSPaV) and six viroids. In addition, a novel viral genome was detected in all four datasets, consisting of a single-stranded, positive-sense RNA molecule of 6033 nucleotides. This genome displays an organization similar to Tymoviridae family members in the Tymovirales order. Nonetheless, the new virus shows enough differences to be considered as a new species defining a new genus. Detection of this new agent in the original grapevines proved very erratic and was only consistent at the end of the growing season. This virus was never detected in the spring period, raising the possibility that it might not be a grapevine-infecting virus, but rather a virus infecting a grapevine-associated organism that may be transiently present on grapevine samples at some periods of the year. Indeed, the Tymoviridae family comprises isometric viruses infecting a wide range of hosts in different kingdoms (Plantae, Fungi and Animalia). The present work highlights the fact that even though HTS technologies produce invaluable data for the description of the sanitary status of a plant, in-depth biological studies are necessary before assigning a new virus to a particular host in such metagenomic approaches.